CLINICAL COURSE OF POLYPOUS RHINOSINUSITIS: CLINICAL ANALYSIS BASED ON INTERNATIONAL CLASSIFICATIONS - Akhmedova Ziyodakhon Anvar qizi (World Scientific Research Journal, 2025)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a complex, relapsing inflammatory condition of the upper airways, substantially affecting patients' quality of life and respiratory function. This study presents a clinical analysis of 120 adult patients diagnosed with CRSwNP according to the EPOS 2020 criteria. We explore demographic characteristics, symptom profiles, endoscopic and imaging findings, laboratory biomarkers, and treatment outcomes over a 12-month follow-up period. Emphasis is placed on differentiating disease endotypes and phenotypes to better predict recurrence and response to therapy, including systemic corticosteroids and biologics. Our findings support the importance of precision medicine approaches in managing this heterogeneous disease.